Chronic uremia attenuates growth hormone-induced signal transduction in skeletal muscle - Sun, Di Fei; Zheng, Zhilan; Tummala, Padmaja; Oh, Jun; Schaefer, Franz; Rabkin, Ralph (Journal of the American Society of Nephrology, 2004)
Malnutrition and muscle wasting are common in chronic renal failure (CRF) and adversely affect morbidity and mortality. Contributing to the muscle wasting is resistance to growth hormone (GH). For testing whether impaired GH signaling is a cause of the skeletal muscle GH resistance and for elucidating its mechanisms, muscle GH signaling and action were studied in GH-deficient rats with surgically induced CRF and sham-operated pairfed control rats.
Gesehen am 15.01.2021